Beberapa Faktor Risiko Kejadian Campak Pada Balita di Kabupaten Sarolangun - Mostang Arianto; Mexitalia Setiawati; Mateus Sakundarno Adi; Suharyo Hadisaputro; Kamilah Budhi (Jurnal Epidemiologi Kesehatan Komunitas, 2018)
Background: Measles is a highly infectious disease caused by the measles virus and is still a health problem in Indonesia. Based on data the communicable disease surveillance system from 2014 to January 2016 have been reported cases of measles as many as 200 cases. This study aims to explain host and environment factors as risk factors for occurrence of measles in children under five years old.Method: A case control study, involving 56 cases children under five years old suffer from measles were registered in form C1 of health center, with 56 sex matched neighborhood controls. Studied variables were analyzed by multivariate.Result: Risk factors for measles occurrence were living at unhealthy house (OR=7.5; 95 % CI=2.64 to 21.19), low of mother’s knowledge (OR=5.7; 95 % CI=2.22 to 14.85), and never received immunization (OR=3.7; 95 % CI=1.45 to 9.39). Risk factors not proved with measles occurrence were malnutrition, lack of vitamin A, never had measles, contact history, breast-fed < 2 years, maternal age < 20 years, low of socio-economic, number of children under five years old at home > 1 and less parenting.Conclusion: Risk factors associated with measles were living at unhealthy house, low ofmother’s knowledge and never received vaccination. For elimination, measles vaccination, home inspection, communication, information and education of measles is required.